Competitive strategies of knowledge and innovation commercialization: a unified swot and fuzzy ahp approach (2017)
Universities have shown a strong desire to commercialize researches and innovations. As a result, they are increasingly weaning themselves from public budgets. Commercialization has become the gateway for privatization, but the improper selection of commercialization strategies often results in the elimination of resources and time. The correct evaluation and ranking of strategies for the best resources is essential for the competitive performance of a university. The hybrid SWOT and Fuzzy AHP model adopted in this study provides a clear categorization of these university strategies. The first and relevant criteria as well as sub-criteria are identified using SWOT analysis. Fuzzy AHP tool is then used to evaluate and rank the internal and external factors that affect competition in Iranian universities. Based on the IE matrix, the growth and the process of building strategies are important priorities when considering commercializing. The results of this study revealed that academic startups, joint technology, joint research laboratories, strategic alliances, recruiting pundit and contracting with industry are the best strategies for Iranian universities.